Most supermassive black hole growth is obscured by dust - Martinez-Sansigre, A; Rawlings, S; Lacy, M; Fadda, D; Marleau, F; Simpson, C; Willott, C; Jarvis, M (2005)
We present an alternative method to X-ray surveys for hunting down the high-redshift type-2 quasar population, using Spitzer and VLA data on the Spitzer First Look Survey. By demanding objects to be bright at 24 microns but faint at 3.6 microns, and combining this with a radio criterion, we find 21 type-2 radio-quiet quasar candidates at the epoch at which the quasar activity peaked. Optical spectroscopy with the WHT confirmed 10 of these objects to be type-2s with 1.4 < z < 4.2 while the rest are blank. There is no evidence for contamination in our sample, and we postulate that our 11 blank-spectrum candidates are obscured by kpc-scale dust as opposed to dust from a torus around the accretion disk. By carefully modelling our selection criteria, we conclude that, at high redshift, 50-80 % of the supermassive black hole growth is obscured by dust.